2019
DOI: 10.1111/birt.12428
|View full text |Cite
|
Sign up to set email alerts
|

Describing latent phase duration and associated characteristics among 1281 low‐risk women in spontaneous labor

Abstract: Background: Recent research suggests that latent phase of labor may terminate at 6 rather than 4 centimeters of cervical dilation. The objectives of this study were to: (a) characterize duration of the latent phase of labor among term, low-risk, United States women in spontaneous labor using the women's self-identified onset; and (b) quantify associations between demographic and maternal/newborn health characteristics and the duration of the latent phase. Methods: This prospective study (n = 1281) described th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…11 These findings are similar to recent European studies on labor duration that used analogous latent phase onset definitions. 15,16 We suspect that these longer latent phase duration estimates predominantly relate to differences in the measurement of latent phase labor onset and contemporary understanding of active labor onset as beginning at six centimeters of cervical dilation 11,15,16 Building on these findings, the purpose of this paper was to evaluate the association between the duration of the latent phase and perinatal processes and outcomes that occurred during active phase, second stage, birth, and the immediate postpartum period. Informed by prior labor duration research, 17 we hypothesized that longer durations of the latent phase of labor would be associated with longer durations of both the active and second stages of labor, greater intervention use, and equivalent morbidity outcomes.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…11 These findings are similar to recent European studies on labor duration that used analogous latent phase onset definitions. 15,16 We suspect that these longer latent phase duration estimates predominantly relate to differences in the measurement of latent phase labor onset and contemporary understanding of active labor onset as beginning at six centimeters of cervical dilation 11,15,16 Building on these findings, the purpose of this paper was to evaluate the association between the duration of the latent phase and perinatal processes and outcomes that occurred during active phase, second stage, birth, and the immediate postpartum period. Informed by prior labor duration research, 17 we hypothesized that longer durations of the latent phase of labor would be associated with longer durations of both the active and second stages of labor, greater intervention use, and equivalent morbidity outcomes.…”
Section: Introductionsupporting
confidence: 88%
“…To address this question, recently published research described latent phase of labor duration and associated characteristics in a sample of low-risk women in spontaneous labor, marking latent phase of labor onset by the time that laboring women reported the start of labor symptoms. 11 This study included women who chose hospital care with certified nurse-midwives (CNMs) and found that the duration of the latent phase was longer than previously estimated in the United States population. 1,3,[11][12][13][14] Among nulliparous women, duration of the latent phase was 9.0 hours at the median and 11.8 hours at the mean; among multiparous women, duration of the latent phase was 6.8 hours at the median and 9.3 hours at the mean.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…. Recent studies showed that in predominantly white, healthy nulliparas, duration of the latent phase of labor was a median duration 9.0 h and mean 11.8 h [4] and self-reported prolonged latent phase that lasted 18 h or more occurred in 29.2% of nulliparas [5]. In Chinese nulliparas, singleton term gestation, spontaneous onset of labor, vaginal delivery, and a normal perinatal outcome, latent phase of labor was 5.1 ± 3.2 h [6].…”
Section: Introductionmentioning
confidence: 99%